DISKRESI (FREIES ERMESSEN): PERANGKAT HUKUM PENUNJANG PEMBANGUNAN - Murtir Jeddawi (Institut Pemerintahan Dalam Negeri, 2017)
Implementation of development requires appropriate legal policy to avoid trapped in collusion, corruption and nepotism. However, it is not uncommon for state officials to hesitate to take a position with the reason